The princess and the pea - Southgate, vera (London : Lady bird Ltd)
The Princess and the Pea is a short but fascinating tale written by the famous Hans Christian Andersen. In his long writing career, Andersen became most famous for his fairy tales, which were read by children all over the world and were translated into more than 40 languages. He wrote over 150 stories for children and thus became one of the world's most important writers. But Andersen's fairy tales were not always world-famous and recognized. Criticism and the public did not pay too much attention to his fairy tales and considered them to be of little value. At first, they were retellings of stories that he had heard and that someone had told him in his childhood, but as time went by, he began to write them himself. He combined fantasy with the real world in the best possible way. The Princess and the Pea is a short but interesting fairy tale about a prince who wanted to marry a real princess. Luck smiled at him and sent a girl who claimed to be the real one. The prince's mother gave the princess a unique test to prove that the girl was a real princess. Namely, under dozens of mattresses and blankets, she placed a single pea to check if the princess would sense it. This story tells us that there are ways to check the true nature of people. It is easy to say that we are one of a kind, but it is more difficult to prove it. In this story, the princess proves her sensitivity, which only a real princess who has been pampered all her life develops. The prince wanted exactly the right princess, so he got one. The story is very short but contains all the elements of a fairy tale. There are no fairies or talking animals, but the most important thing each fairy tale has - a prince, a princess, and a moral of the story. The anecdote is simple and intended for the youngest because there are no negative elements or scary parts.
Fiction English book
Keywords: English - Fiction Book